Diversity of Actinobacteria in Algerian Saharan soil and description of sixteen new taxa (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The goal of this study was to investigate the biodiversity of actinobacteria in Algerian Saharan soils by using a polyphasic taxonomic approach based on the phenotypic and molecular studies (16S rRNA gene sequence analysis and DNA-DNA hybridization).A total of 323 strains of actinobacteria were isolated from different soil samples, by a dilution agar plating method, using selective isolation media without or with 15-20% of NaCl (for halophilic strains). The morphological and chemotaxonomic characteristics (diaminopimelic acid isomers, whole-cell sugars, menaquinones, cellular fatty acids and diagnostic phospholipids) of the strains were consistent with those of members of the genus Saccharothrix, Nocardiopsis, Actinopolyspora, Streptomonospora, Saccharopolyspora, Actinoalloteichus, Actinokineospora and Prauserella.The 16S rRNA gene sequence analysis of 15 selected strains isolated from different soil samples of Adrar (SA152, SA233 and B32), Biskra (H254), Djelfa (H27), Ouargla (H19), El-Oued (H23 and H32), Ghardaïa (H53, H55, PAL84 and H225) and Tamanrasset (SA181, SA198 and AH97) showed that each strain formed a distinct phyletic line within the radiation of the most closely related genus: SA233, SA152, SA181 and SA198 with Saccharothrix, B32 with Nocardiopsis, H19, H23, H32, H55 and H254 with Actinopolyspora, H27 with Streptomonospora, H53 with Saccharopolyspora, AH97 with Actinoalloteichus, PAL84 with Actinokineospora and H225 with Prauserella. Furthermore, the result of DNA–DNA hybridization (DDH) between each strain and the nearest species was clearly below the 70% threshold considered for the delineation of separate species. The genotypic and phenotypic data confirmed that these actinobacteria represent five novel species of the genus Actinopolyspora named Actinopolyspora algeriensis, A. saharensis, A. righensis, A. mzabensis and A. biskrensis, respectively with the type strains H19T (DSM 45476T), H32T (DSM 45459T), H23T (DSM 45501T), H55T (DSM 45460T) and H254T (DSM 46684T). Moreover, four new species of Saccharothrix: Saccharothrix algeriensis, S. saharensis, S. hoggarensis and S. tamanrassetensis, were described, respectively with the type strains SA233T (DSM 44581T), SA152T (DSM 45456T), SA181T (DSM 45457T) and SA198T (DSM 45947T). In addition, six new species: Nocardiopsis algeriensis B32T (DSM 45462T), Streptomonospora algeriensis H27T (DSM 45604T), Saccharopolyspora ghardaiensis H53T (DSM 45606T), Actinoalloteichus hoggarensis AH97T (DSM45943T), Actinokineospora mzabensis PAL84T (DSM 45961T) and Prauserella isguenensis H225T (DSM 46664T) were also reported in this study.On the other hand, a new strain designated H195T was isolated from Ghardaïa. The comparative analyses of the 16S rRNA gene sequence and nucleotide signatures (along with phenotypic and chemotaxonomic properties) of this strain revealed that it is different from all known actinobacterial genera. Based on these results, this strain: H195T (DSM 46680T) represents a novel genus and species, named Mzabimyces algeriensis gen. nov., sp. nov., within a new family, Mzabimycetaceae fam. nov. In total, 16 new taxa were described in this study. Keywords: Biodiversity, Actinobacteria, Saharan soil, Algeria, new taxa.